Principles of Business Activity in the Context of Sustainable Development - Калаченкова, Катерина Олександрівна; Калаченкова, К. О.; Калаченкова, Екатерина Александровна; Kalachenkova, Kateryna O.; Мельник, Світлана Борисівна; Мельник, С. Б.; Мельник, Светлана Борисовна; Melnyk, Svitlana B.; Павлюченко, Юлія Миколаївна; Павлюченко, Ю. М.; Павлюченко, Юлия Николаевна; Pavliuchenko, Yuliia M.; et al. (Springer Nature, 2021)
Scientific research is based on the fact that the business activity of subjects is one of the key elements in achieving sustainable development goals. Considering that business activity is carried out on the basis of certain principles, the authors believe that the goals of sustainable development have an impact on the modernisation and the formation of new principles of business activity. Compliance with these principles contributes to the actualisation of the business (economic) turnover in modern reality. The aim of the article is to substantiate the formation of new principles of business activity of subjects as the main guiding principles of its implementation and appropriate regulation in the context of sustainable development. This study aims to prove that the following elements can be considered the new principles of management: a) ensuring the vital interests of entrepreneurs, consumers and society in information environment; b) corporate social responsibility; c) fair competition in entrepreneurship; d) corporate greening. To achieve this goal, the authors provided the characteristics of these principles and analysed the current state of their application. To solve the problem, first, the relationship between the listed principles and the goals of sustainable development is analysed. And secondly, the analysis of the influence of each of the principles on business activity is carried out. While conducting the scientific research, methods such as dialectical, system-structural analysis, formal-legal, comparative, as well as other methods and scientific approaches were used to achieve the goal of the study. In the course of the study, it was substantiated that the listed principles fully fit into the concept of sustainable development, which includes economic, social and environmental components. The conclusions summarise the characteristics of each of the new principles of business activity. Also, recommendations were formulated regarding the optimisation of the regulatory consolidation and the practical implementation of these economic principles, taking into account the European and Ukrainian experience. The results of the study are important for theory and practice, since they regard the presented principles as those that can be used to assess the activities of specific business entities, as well as the state of legislation and government policy. The obtained results of the assessment can be used to develop proposals for improving the legal regulation and state policy of the economic sphere (including business and entrepreneurial activity).

Наукові дослідження ґрунтуються на тому, що ділова активність суб’єктів є одним із ключових елементів у досягненні цілей сталого розвитку. Враховуючи, що підприємницька діяльність здійснюється на основі певних принципів, автори вважають, що цілі сталого розвитку впливають на модернізацію та формування нових принципів підприємницької діяльності. Дотримання цих принципів сприяє актуалізації ділового (господарського) обороту в сучасних реаліях. Метою статті є обґрунтування формування нових засад підприємницької діяльності суб’єктів як основних керівних принципів її реалізації та відповідного регулювання в контексті сталого розвитку. Це дослідження має на меті довести, що такими елементами можна вважати нові принципи управління: а) забезпечення життєво важливих інтересів підприємців, споживачів та суспільства в інформаційному середовищі; б) корпоративна соціальна відповідальність; в) чесна конкуренція у підприємництві; г) корпоративне озеленення. Для досягнення цієї мети автори навели характеристику цих принципів та проаналізували сучасний стан їх застосування. Для вирішення проблеми спочатку аналізується взаємозв'язок між перерахованими принципами та цілями сталого розвитку. А по-друге, проводиться аналіз впливу кожного з принципів на підприємницьку діяльність. При проведенні наукового дослідження для досягнення мети дослідження були використані такі методи, як діалектичний, системно-структурний аналіз, формально-правовий, порівняльний, а також інші методи та наукові підходи. У ході дослідження було обґрунтовано, що перераховані принципи повністю вписуються в концепцію сталого розвитку, яка включає економічну, соціальну та екологічну складові. У висновках узагальнено характеристики кожного з нових принципів підприємницької діяльності. Також сформульовано рекомендації щодо оптимізації нормативного закріплення та практичної реалізації цих економічних принципів з урахуванням європейського та українського досвіду. Результати дослідження є важливими для теорії та практики, оскільки розглядають викладені принципи як такі, які можуть бути використані для оцінки діяльності конкретних суб’єктів господарювання, а також стану законодавства та державної політики. Отримані результати оцінки можуть бути використані для розробки пропозицій щодо вдосконалення правового регулювання та державної політики економічної сфери (включаючи комерційну та підприємницьку діяльність).
Kalachenkova K. Principles of Business Activity in the Context of Sustainable Development / K. Kalachenkova, S. Melnyk, Yu. Pavliuchenko, O. Titova, R. Kvasnytska // Part of the Lecture Notes in Networks and Systems book series: The Importance of New Technologies and Entrepreneurship in Business Development: In The Context of Economic Diversity in Developing Countries. - LNNS, volume 194. - P. 273 – 285.
Keywords: Corporate Greening Process; corporate social responsibility; economic competition; information environment; limitation of economic competition; principles of business activity; sustainable development; корпоративний процес екологізації; корпоративна соціальна відповідальність; економічна конкуренція; інформаційне середовище; обмеження економічної конкуренції; принципи ділової активності; сталий розвиток; Research Subject Categories::SOCIAL SCIENCES::Business and economics